To What Extent, And Why, Are Climate Projections For The 21st Century Uncertain And Does The Uncertainty Matter? - Draz, Omar (Migration Letters, 2024)
Uncertainties in global and regional future climate change has got attention to a great extent. Greenhouse gas (GHG) emissions scenario, modelling design and biases, internal climate volatility due to irregular pattern of the earth’s climate are specifically named as sources of uncertainty. Different parameters like time scale of projections and multiple variables have significant role in identifying the key sources of uncertainty in the 21st century climate projections. Concerning climate change over such a long time period, scenario and model design uncertainty tends to predominate particularly at the worldwide scale. For shorter-term forecasts and higher-order climatic statistics, internal variability becomes increasingly important in first few decades of the 21st century. These uncertainties need a probabilistic rather than deterministic approach to the climate forecast issue. This paper highlights Knowledge Uncertainty that is attributable to our limited understanding and misrepresentation of the situation and the Intrinsic Uncertainty that is inherently connected to the problem itself. While the first may be dealt with by better scientific understanding and the later needs to be defined as thoroughly as possible so that all consequences are taken into consideration. The main analysis of the paper is on the key sources of uncertainty in future climate projections.